2014
DOI: 10.1590/1516-635x1603279-284
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic, probiotic and symbiotic as alternative to Antibiotics on the Performance and Immune Response of Broiler Chickens

Abstract: This study aimed to evaluate diets supplemented with prebiotic, probiotic and symbiotic as an alternative to antibiotics on the performance and immune response against the virus of Newcastle disease in broiler chickens. 1,400 one-day old male Cobb 500 chicks were raised until 42 days old in a completely randomized design with 2x2+1 factorial scheme with seven replications. The treatments were: diet without supplementation (base diet -BD), BD + prebiotic, BD + probiotic, BD + symbiotic (prebiotic + probiotic), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
1
5
0
1
Order By: Relevance
“…Prebiotics are nondigestible fiber compounds that reduce the pathogenic bacteria through competing for binding sites on the intestinal mucosa and enhance the survival and growth of beneficial microbial species in the gut [21,22]. Several studies have shown a promise outcome to use synbiotics as antibiotic replacements in commercial broiler chickens under thermoneutral temperatures [23][24][25], although some contrasting results have been reported [26,27]. The inconsistent results could be affected by multiple factors such as the birds' age and strain with different survivability, diet quantities and nutrients, and the format of synbiotics and dosage used between the different studies [28].…”
Section: Introductionmentioning
confidence: 99%
“…Prebiotics are nondigestible fiber compounds that reduce the pathogenic bacteria through competing for binding sites on the intestinal mucosa and enhance the survival and growth of beneficial microbial species in the gut [21,22]. Several studies have shown a promise outcome to use synbiotics as antibiotic replacements in commercial broiler chickens under thermoneutral temperatures [23][24][25], although some contrasting results have been reported [26,27]. The inconsistent results could be affected by multiple factors such as the birds' age and strain with different survivability, diet quantities and nutrients, and the format of synbiotics and dosage used between the different studies [28].…”
Section: Introductionmentioning
confidence: 99%
“…The use of synbiotics has the advantage that it can increase the survival of probiotic bacteria due to the specific substrate available for fermentation so that the body gets more perfect benefits (Hamid et al, 2014). In addition, synbiotics are also useful for increasing immunity and production performance in poultry (Murarolli et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Next to improvement of intestinal function itself, dietary nondigestible carbohydrates may also have systemic effects and modulate the immune system in both animals and humans. These nondigestible carbohydrates might stimulate the immune system via cytokine expression. Little research is conducted on the direct effects on cytokine expression, but many studies have assessed indirect effects through stimulation of beneficial micro-organisms and their metabolism in the gut .…”
Section: Introductionmentioning
confidence: 99%